2021
DOI: 10.1080/26410397.2021.1933815
|View full text |Cite
|
Sign up to set email alerts
|

Understanding factors associated with continuation of intrauterine device use in Gujarat and Rajasthan, India: a cross-sectional household study

Abstract: The Government of India has promoted the expansion of access to and uptake of intrauterine devices (IUDs), during both the interval (IIUD) and postpartum (PPIUD) periods, as part of its Family Planning 2020 initiative. This study, conducted by EngenderHealth as part of the Expanding Access to IUD Services in India project, examines IIUD and PPIUD continuation rates over time and investigates factors associated with IUD continuation. We recruited respondents (N = 5024) through a repeated cross-sectional househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
2
8
0
1
Order By: Relevance
“…We used ML models with iterative thematic analysis to explore potential predictors of IUD use among currently married women in India and found that the strongest predictor of this outcome was shared marital family planning goals in terms of both contraceptive decision-making and fertility goals. This finding corresponds with a smaller study from Rajasthan, India, that indicates that joint marital decision-making regarding contraceptive use among IUD users is associated with IUD continuation ( Singal et al, 2022 ). However, it is not in line with research from younger married women from Maharashtra, India, which found a trend in the association between IPV and IUD use, or with a state-representative sample of married women aged 15–49 in Uttar Pradesh that found an association between reproductive coercion and IUD use ( Chen et al, 2020 ; Tomar et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We used ML models with iterative thematic analysis to explore potential predictors of IUD use among currently married women in India and found that the strongest predictor of this outcome was shared marital family planning goals in terms of both contraceptive decision-making and fertility goals. This finding corresponds with a smaller study from Rajasthan, India, that indicates that joint marital decision-making regarding contraceptive use among IUD users is associated with IUD continuation ( Singal et al, 2022 ). However, it is not in line with research from younger married women from Maharashtra, India, which found a trend in the association between IPV and IUD use, or with a state-representative sample of married women aged 15–49 in Uttar Pradesh that found an association between reproductive coercion and IUD use ( Chen et al, 2020 ; Tomar et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…Findings from our study are aligned with prior research that documents higher IUD use among wealthier and more educated women as well as those with greater contraceptive knowledge ( Bhat & Halli, 1998 ; Kumar et al, 2018 ; Singal et al, 2022 ). This underscores that community-level support may be particularly important for lower-resource communities to increase their IUD uptake.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The 33 full-text documents retained for this scoping review included three theoretical and/or conceptual articles [1,3,6] and three systematic reviews [7,23,25]. Eight studies focused on women's experiences with family planning counselling and counselling preferences [2,4,9,[26][27][28][29][30], one study discussed the process of contraceptive decision-making [5], and five studies focused on measurement of patient-centred family planning care [10,[31][32][33][34]. Only 13 studies discussed a tool for patient-centred family planning care.…”
Section: Characteristics Of the Included Literaturementioning
confidence: 99%
“…Adanya peran tenaga kesehatan melalui konseling, penyuluhan, pemberian informasi kesehatan terkait mitos-mitos negatif kontrasepsi IUD melalui pemanfaatan berbagai media akan membantu meningkatkan kesadaran wawasan serta kesadaran ibu dalam penggunaan kontrasepsi yang lebih efektif (Woldeyohannes et al, 2022). Pemberian konseling yang berkualitas sangat penting untuk memenuhi hak reproduksi akseptor termasuk penggunaan kontrasepsi IUD (Singal et al, 2022).…”
Section: Analisis Bivariat Hubungan Peran Tenaga Kesehatan Dengan Min...unclassified